The Effect of Total Quality Management (TQM) on Organizational Performance: A Case Study - Hamidreza Fooladgar; Alireza Khojasteh Pour (International Journal of Supply Chain Management, 2022)
Abstract—TQM as a management paradigm has been accepted by many organizations around the world. TQM is an organization that attempts to make the structures, procedures, customs, behavior and even their infrastructure in order to maintain customer satisfaction, coupled with the emphasis on compatibility, quality improvement and organizational competitiveness improvement. So, this study aimed to examine the impact of TQM principles on organizational performance. The study was conducted in Industrial Services Engineering Company of Iran Khodro (ISEIKCO), the study sample size was 272 managers and experts from different levels. The researcher depended on primary and secondary data. The results show that TQM has positive impact on organizational performance. In light of these findings, the study provided a set of recommendations.